Codeswitching: A Bilingual Toolkit for Opportunistic Speech Planning - Beatty-Martínez, Anne L.; Navarro-Torres, Christian A.; Dussias, Paola E. (Frontiers in Psychology, 2020)
The ability to engage in fluent codeswitching is a hallmark of the flexibility and creativity of bilingual language use. Two discoveries have changed the way we think about codeswitching and its implications for language processing and language control. One is that codeswitching is not haphazard, but subject to unique linguistic and cognitive constraints. The second is that not all bilinguals codeswitch, but those who do, exhibit usage patterns conforming to community-based norms. However, less is known about the cognitive processes that regulate and promote the likelihood of codeswitched speech. Together with recent empirical studies, we provide corpus evidence that highlights how codeswitching serves as an opportunistic strategy for optimizing performance in cooperative communication. From this perspective, codeswitching is part and parcel of a toolkit available to bilingual codeswitching speakers to assist in language production by allowing both languages to remain active and accessible, and therefore providing an alternative means to convey meaning, with implications for bilingual speech planning and language control more generally.